2019
DOI: 10.3389/fgene.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Hub Genes for Heat Tolerance in Water Buffalo (Bubalus bubalis) Using Transcriptome Data

Abstract: Heat stress has a detrimental effect on the physiological and production performance of buffaloes. Elucidating the underlying mechanisms of heat stress is challenging, therefore identifying candidate genes is urgent and necessary. We evaluated the response of buffaloes (n = 30) to heat stress using the physiological parameters, ELISA indexes, and hematological parameters. We then performed mRNA and microRNA (miRNA) expression profiles analysis between heat tolerant (HT, n = 4) and non-heat tolerant (NHT, n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 96 publications
3
20
0
Order By: Relevance
“…Verma et al [30] determined RR and RT as the most sensitive indices of heat tolerance among all the physiological reactions studied. This study showed that the RT and RR in HT individuals were significantly lower when compared to NHT, similar to observation in cattle [31] and buffalo [32]. Elevated temperature increased the plasma HSP90 and HSP70 levels more markedly in HT than in NHT individuals, coinciding to previous study in cattle [33] and rodents [34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Verma et al [30] determined RR and RT as the most sensitive indices of heat tolerance among all the physiological reactions studied. This study showed that the RT and RR in HT individuals were significantly lower when compared to NHT, similar to observation in cattle [31] and buffalo [32]. Elevated temperature increased the plasma HSP90 and HSP70 levels more markedly in HT than in NHT individuals, coinciding to previous study in cattle [33] and rodents [34].…”
Section: Discussionsupporting
confidence: 90%
“…A limited number of animals may limit the power of design as well as validity of results. However, several studies published previously using even the fewer animals compared with our study [32,55]. The results of our study are giving foundation for heat tolerance mechanism in dairy cows.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…MicroRNAs play a significant role during follicle development in bovine 21 , 22 . In buffalo, heat stress was observed to alter the blood miRNA and mRNA content 23 . The role of miRNAs is also demonstrated in the regulation of lactating physiology in the buffalo mammary gland 24 , and miRNA expression changes were observed in buffalo corpus luteum during pregnancy 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Through a weighted gene co‐expression network analysis, they identified a set of 12 hub genes ( BNIPL , TUBA1C , C2CD4B , DCP1B , MAP3K5 , PDCD11 , SRGAP1 , GDPD5 , BARX2 , SCARA3 , CTU2 and RPL27A ) involved in several pathways related to milk production. With a similar approach, the mRNA and microRNA expression profiles of heat‐tolerant and non‐heat‐tolerant buffaloes have been analysed (Liu et al ). The analysis highlighted a total of 753 differentially expressed genes and 16 microRNAs differentially expressed between the two groups of animals.…”
Section: Introductionmentioning
confidence: 99%